Analysis of Age, Gender and H Analysis of Age, Gender and Hearing Loss in Early Stage Drug-Resistant TB Patients at Abdul Wahab Sjahranie Hospital Samarinda - Rio Mandala Putra Ruslan; Moriko Pratiningrum; Eva Rachmi (Jurnal Ilmu Kesehatan, 2021)
ABSTRACT Hearing loss is one of the side effects of using kanamycin. Hearing loss will reduce the ability to receive information and verbal communication which will interfere with daily activities. This study aims to determine the relationship between age, sex on hearing loss and hearing loss in patients with drug-resistant TB during kanamycin treatment. The design of this study was cross sectional using purposive sampling. The number of samples that met the inclusion and exclusion criteria was 12 patients. The results show that hearing loss is not related to age (p = 0.293), sex (p = 1,000), and hearing loss (p = 0.182). Based on the results of this study it can be concluded that there is no relationship between age, sex on hearing loss and hearing loss during kanamycin administration. Keywords: Hearing Loss, Age, Sex